2019
DOI: 10.2188/jea.je20170341
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Daily Walking Time With Pneumonia Mortality Among Elderly Individuals With or Without a Medical History of Myocardial Infarction or Stroke: Findings From the Japan Collaborative Cohort Study

Abstract: Background The association between daily walking and pneumonia mortality, stratified by the presence of disease conditions, such as myocardial infarction (MI) or stroke, was investigated. Methods The study participants were 22,280 Japanese individuals (9,067 men and 13,213 women) aged 65–79 years. Inverse propensity weighted competing risk model was used to calculate the hazard ratio (HR) and 95% confidence interval (CI) for pneumonia mortality. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Part of the problem is that higher-level injuries result in loss of innervation to motor neurons that innervate the diaphragm and intercostal muscles, resulting in compromised respiratory motor control (reviewed in [ 18 ]). The lack of mobility in SCI persons also exacerbates this issue since exercise, like walking and running, has been shown to reduce pneumonia-related mortality [ 19 , 20 , 21 , 22 ]. However, what may make respiratory infections particularly deadly for SCI persons is that higher injuries above the level of thoracic segment 6 (T6) result in disruption of descending supraspinal input to sympathetic preganglionic neurons (SPNs) that innervate immune organs and modulate immune function, which we describe in more detail in a later section.…”
Section: The Consequences Of Peripheral Immune Dysfunctionmentioning
confidence: 99%
“…Part of the problem is that higher-level injuries result in loss of innervation to motor neurons that innervate the diaphragm and intercostal muscles, resulting in compromised respiratory motor control (reviewed in [ 18 ]). The lack of mobility in SCI persons also exacerbates this issue since exercise, like walking and running, has been shown to reduce pneumonia-related mortality [ 19 , 20 , 21 , 22 ]. However, what may make respiratory infections particularly deadly for SCI persons is that higher injuries above the level of thoracic segment 6 (T6) result in disruption of descending supraspinal input to sympathetic preganglionic neurons (SPNs) that innervate immune organs and modulate immune function, which we describe in more detail in a later section.…”
Section: The Consequences Of Peripheral Immune Dysfunctionmentioning
confidence: 99%
“…Our study implies that the absolute benefit for older individuals with CVDs from engaging in physical activity would be much greater. Taken together with previous findings showing mortality benefits in older population, 13 health professionals should encourage older individuals with CVDs to engage in physical activity to improve outcomes from LoRI.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies on respiratory tract infection and physical activity are mostly for general population and mainly focused on upper respiratory tract infection with a benign clinical course. 11 , 12 , 13 , 14 , 15 , 16 , 17 Among the studies on LoRI, inconsistent data exist. 11 , 12 , 13 , 15 Specifically, it is not clear whether a low level of physical activity, performed less than the minimum amount suggested in the guidelines, 5 , 6 could lower the risk of LoRI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] Previous studies have shown that daily walking habit and early rehabilitation are associated with a decline in mortality rate among patients with pneumonia. 6,7 Identification of prognostic factors is important for future initiatives to reduce the readmission and mortality rates and target the resources for those at highest risk.…”
Section: Introductionmentioning
confidence: 99%